Figuras da tradição judaico-cristã n’a demanda do Santo Graal: os rastros míticos da mulher de Salomão e da irmã de Persival - Silva, Alessandra Fabrícia Conde da (2018)
I perceive the Judaeo-Christian tradition as more comprehensive than it is treated in the biblical canon. This work aims to unfold paths undertaken by some Judaeo-Christian myths, that is, mythical structures, which corroborated the construction of new myths, such as those of Percival’s sister and Solomon’s wife – characters of A demanda do Santo Graal (1995), Portuguese translation from the 15th century, copy of a French sample from the 18th century. In this trajectory, it is essential to consider, besides the biblical scripture, some apocryphal manuscripts which lend literary elements of feminine prominence and humility to the matter of Britain. This character, for example, was scarcely referred in the Portuguese Demand; therefore it is essential that La queste del Saint Graal (1923), present in Vulgata, be consulted for the purpose of studying the narrative of Solomon’s wife. Thus, according to the Judaeo-Christian tradition one can attest that the elements borrowed from it, still echo in discourses, which sometimes vilify and sometimes defend women, making them exemplary and heroic feminine figures, despite carrying the heavy burden of anti feminine tradition. Such misogynous burden is noticed in the narratives that aim at legitimating the Grail’s hero lineage, taking the Hebrew kings from the biblical tradition as ancestors. It is from this androcentric nucleus that heroic feminine narratives will emerge, softening the bitterness against women, in the moment heroes find themselves in abulia in face of the unknown. For this purpose, the dissertation carries out an analytical study of the referred literary pieces, following the methodological procedures of bibliographic, qualitative research, identifying the literary, sociological, historical and cultural perspectives. It tried to unveil the paths taken by the characters Percival’s sister and Solomon’s wife, along their mythical trajectory, compatible to the Judaeo- Christian tradition.